Complicated Scenarios of Transitions to Deterministic Chaos in Non-Ideal Dynamic Systems - Shvets, Aleksandr Yu.; Sirenko, Vasiliy (NTU "KhPI", 2016)
Some of non-ideal dynamic systems are considered. It is discovered and described the complicated transition scenarios from regular to chaotic regimes and transitions between different types of chaotic regimes. Described the transition to chaos, which begins by the Feigenbaum scenario, and ends by intermittency. Also discusses the scenario of intermittency with several laminar phases and one turbulent phase. It is discovered and described transitions "hyperchaotic attractor of one type – hyperchaotic attractor of another type," which are realized according to the scenario of a generalized intermittency, but only with two rough-laminar phases.
Keywords: chaotic simulation; chaotic and hyperchaotic attractor; scenario of transition to chaos